Rancang Bangun Media Pembelajaran IPS Berbasis Google Sites Materi Proklamasi Kemerdekaan Indonesia - Yona Wahyuningsih; Vian Yulianty (Jurnal Lensa Pendas, 2023)
This research is motivated by optimizing the material for the proclamation of Indonesian independence in the fifth grade of elementary school in social studies learning -based media Google Sites. The use of technology in the use of learning media by teachers is one form of effort to achieve learning success. This research is a development research that develops media based Google Sites in social studies learning in fifth grade elementary school. The research method uses the D&D (Design & Development) method with research stages based on the ADDIE development model which consists of 5 stages, namely Analyze (Analysis), Design(Design), Development (Development), Implementation (Implementation), and Evaluation (Evaluation). Data collection techniques using interviews and questionnaires. The results of the development of Google Sites get an "excellent" interpretation from the assessment of linguists, media experts, and material experts. Based on the results of the assessment and user responses, namely teachers and students of class V, the Google Sites received an "excellent" interpretation and was suitable for use in learning based on indicators of material content, presentation, language, appearance, and media quality.